PENGGUNAAN MEDIA KARTU DOMINO UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS III PEMBELAJARAN IPAS SEKOLAH DASAR - Julia Dewi Puspita Sari; Muhammad Thamrin Hidayat; Asmaul Lutfauziah; Akhwani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Low student learning outcomes in science and science subjects in elementary schools are caused by the use of conventional learning media. This study aims to determine the use of domino cards to improve student learning outcomes. This research used a quantitative approach with a pre-experimental one-group pretest-posttest design. The study was conducted at Nurul Ulum Elementary School in Surabaya, with 32 third-grade students as subjects. Learning outcomes were analyzed using the N-Gain formula. The results showed that the use of domino cards can improve learning outcomes. The average N-Gain value for cognitive learning outcomes was 0.87, which is considered a high improvement. Furthermore, the average psychomotor learning outcome was 98.12. Thus, domino cards can improve science and science learning outcomes in elementary schools.